Understanding and utilizing best practice strategies for facilitating online learning - Weidner, Thomas G.; Armstrong, Kirk J. (Sports medicine and exercise science in video, 2009)
Distance education has grown from a simple form of correspondence to a highly sophisticated synchronous and asynchronous interactive online learning environment. As technology has advanced, the online delivery of entry-level and continuing athletic training education courses has also increased. In fact, an online component has been added to many traditional athletic training courses to supplement classroom instruction methods, a feature that allows students the ability to participate in learning activities that would otherwise not be possible in the classroom. As such, it is imperative that instructors and learners possess a basic understanding of the pedagogical and learning differences of the online environment. In that regard, Understanding and Utilizing Best Practice Strategies for Facilitating Online Learning provides an overview of best practice strategies for facilitating online learning to meet the educational needs of their learners. The video highlights the important pedagogical differences between online learning and traditional classroom learning (id est, quality/quantity of interactions, responsibility of instructor and learners) in order to foster a better understanding of the framework of online learning.